Kepastian Hukum Akibat Kelalaian Jaksa Penuntut Umum - Elizabeth, Vivi; Adhari, Ade (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
The presence of legal uncertainty in the Ngabang District Court Decision No. 48/Pid.Sus/2019/PN.Nba raises questions about the impact of the Public Prosecutor's negligence in determining the charges. In this case, the prosecutor failed to establish charges that corresponded to the defendant's actions, necessitating a review of the legal certainty affected by such negligence. This research is categorized as a library study with a qualitative approach. The methodology used is normative analysis, focusing on analyzing and evaluating the impact of the prosecutor's negligence in establishing charges. The findings conclude that the Public Prosecutor's negligence in determining the appropriate charges leads to legal uncertainty, the violation of human rights, and disorder. It also limits the authority of the judicial panel. Therefore, the Public Prosecutor must exercise greater caution in selecting charges, as the indictment plays a crucial role in the judicial process.